Adaptive position feedback consensus of networked robotic manipulators with uncertain parameters and communication delays - Wang, Lijiao; Meng, Bin (IET control theory & applications, 2015)
In this study, the authors address the leaderless consensus problem of multiple robotic manipulators with communication delays. Taking dynamic uncertainties of the robotic agents into consideration, they perform the distributed adaptive position feedback control scheme design for strongly connected information topology, where the communication is subject to constant and bounded time delays. The novel distributed sliding observer is first proposed such that the joint velocities can be estimated online. Then, the distributed adaptive controller with dynamic parameter updating is constructed based on the observed information. The convergence of consensus errors is proved with Lyapunov stability analysis tool. Finally, simulations are performed on networked robotic manipulators to validate the effectiveness of the theoretical approach.